2012
DOI: 10.1161/atvbaha.112.300497
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 Is Regulated by p75 Neurotrophin Receptor and Predicts Mortality in Diabetic Patients With Critical Limb Ischemia

Abstract: Objective-The p75 neurotrophin receptor (p75 NTR ) contributes to diabetes mellitus−induced defective postischemic neovascularization. The interleukin-33 receptor ST2 is expressed as transmembrane (ST2L) and soluble (sST2) isoforms. Here, we studied the following: (1) the impact of p75 NTR in the healing of ischemic and diabetic calf wounds; (2) the link between p75 NTR and ST2; and (3) circulating sST2 levels in critical limb ischemia (CLI) patients. Methods and Results-Diabetes mellitus was induced in p75NTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 48 publications
3
31
0
1
Order By: Relevance
“…However, in skin wounds of diabetic mice, IL-17 was not decreased in a similar fashion as RegIIIγ, suggesting that IL-17 was not a cytokine that led to decreased REG3A in diabetic skin wounds. Although we further screened multiple cytokines and found that both IL-33 and IL-36γ induced REG3A expression in keratinocytes, only IL-33 was decreased as similar as RegIIIγ in diabetic skin wounds, which was consistent with the previous report that IL-33 was decreased in diabetic skin wounds34. We then confirmed that decreased REG3A expression was possibly due to decreased IL-33 in diabetic skin wounds, as the administration of IL-33 into the dorsal skin of diabetes restored RegIIIγ expression.…”
Section: Discussionsupporting
confidence: 90%
“…However, in skin wounds of diabetic mice, IL-17 was not decreased in a similar fashion as RegIIIγ, suggesting that IL-17 was not a cytokine that led to decreased REG3A in diabetic skin wounds. Although we further screened multiple cytokines and found that both IL-33 and IL-36γ induced REG3A expression in keratinocytes, only IL-33 was decreased as similar as RegIIIγ in diabetic skin wounds, which was consistent with the previous report that IL-33 was decreased in diabetic skin wounds34. We then confirmed that decreased REG3A expression was possibly due to decreased IL-33 in diabetic skin wounds, as the administration of IL-33 into the dorsal skin of diabetes restored RegIIIγ expression.…”
Section: Discussionsupporting
confidence: 90%
“…The Dallas Heart Study revealed a significant association of sST2 with markers of inflammation; furthermore, sST2 was highly associated with all-cause mortality and cardiovascular mortality [33]. Another study showed elevated levels of sST2 in diabetic patients with critical limb ischemia, again predicting mortality in those patients [34]. Correspondingly, our study also showed a significant elevation of sST2 in LC, primarily a nontumor condition.…”
Section: Il-33/sst2 Ratiosupporting
confidence: 72%
“…It was beyond the scope of this experiment to assess factors related to vascular remodelling, thus we cannot rule out the influence of pathways related to structural alterations, such as the interleukin-33/ST2 receptor pathway [43], metalloproteinases and vascular endothelial growth factor [44].…”
Section: Study Limitationsmentioning
confidence: 99%